Functionalized Silver and Gold Nanomaterials with Diagnostic and Therapeutic Applications - Rabiee, Navid; Ahmadi, Sepideh; Iravani, Siavash; Varma, Rajender S (Pharmaceutics, 2022)
The functionalization of nanomaterials with suitable capping ligands or bioactive agents is an interesting strategy in designing nanosystems with suitable applicability and biocompatibility; the physicochemical and biological properties of these nanomaterials can be highly improved for biomedical applications. In this context, numerous explorations have been conducted in the functionalization of silver (Ag) and gold (Au) nanomaterials using suitable functional groups or agents to design nanosystems with unique physicochemical properties such as excellent biosensing capabilities, biocompatibility, targeting features, and multifunctionality for biomedical purposes. Future studies should be undertaken for designing novel functionalization tactics to improve the properties of Au- and Ag-based nanosystems and reduce their toxicity. The possible release of cytotoxic radicals or ions, the internalization of nanomaterials, the alteration of cellular signaling pathways, the translocation of these nanomaterials across the cell membranes into mitochondria, DNA damages, and the damage of cell membranes are the main causes of their toxicity, which ought to be comprehensively explored. In this study, recent advancements in diagnostic and therapeutic applications of functionalized Au and Ag nanomaterials are deliberated, focusing on important challenges and future directions.
Keywords: cancer theranostics; gold nanomaterials; drug delivery; silver nanomaterials; functionalization; biosensing